Design and optimization of metal structures - Farkas, József, 1944- (Horwood Pub., 2008)
An industrial book that analyses various theoretical problems, optimizes numerical applications and addresses industrial problems such as belt-conveyor bridge, pipeline, wind turbine power, large-span suspended roof and offshore jacket member. Multi-storey frames and pressure vessel-supporting frames are discussed in detail. The book's emphasis is on economy and cost calculation, making it possible to compare costs and make significant savings in the design stages, by, for example, comparing the costs of stiffened and un-stiffened structural versions of plates and shells. In this respect, this book will be an invaluable aid for designers, students, researchers and manufacturers to find better, optimal, competitive structural solutions. Emphasis is placed on economy and cost calculation, making it possible to compare costs and make significant savings in the design stages of metal structuresOptimizes numerical applications and analyses various theoretical and industrial problems, such as belt-conveyor bridge, pipeline, wind turbine power, large-span suspended roof and offshore jacket memberAn invaluable aid for designers, students, researchers and manufacturers to find better, optimal, competitive structural solutions.
Keywords: Building, Iron and steel.; Structural engineering.; elektronické knihy; electronic books